2021
DOI: 10.3390/en14175448
|View full text |Cite
|
Sign up to set email alerts
|

Selected Issues on Material Properties of Objects in Computer Simulations of Floodlighting

Abstract: This paper addresses issues with computer simulation involved in designing illumination for architectural structures. In particular, the reflectance and transmittance of materials were studied with respect to their influence on luminance values, thus directly the power levels for luminaires applied under particular projects. Raster images derived from digitally processed daytime pictures were used to precisely define material properties. Bitmaps were tested with regard to measuring and editing materials with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This feature is primarily due to the need to build a three-dimensional geometric model of the object intended for lighting. It is estimated that making a three-dimensional geometric model of an object used as a basis for a lighting design constitutes about 70% of the overall designer's working time [6]. The final effect of the simulation work depends on the quality of the 3D model [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature is primarily due to the need to build a three-dimensional geometric model of the object intended for lighting. It is estimated that making a three-dimensional geometric model of an object used as a basis for a lighting design constitutes about 70% of the overall designer's working time [6]. The final effect of the simulation work depends on the quality of the 3D model [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a different point and direction of observation of the object do not adversely affect the accuracy of the project made in this way. Research has shown [6,15] that traceability, whether in computer graphics or reality, results only from how the collage is generated. When analysing the image in Figure 3, if we are only guided by the idea of the object generated by the computer and the real object, without taking into account the surroundings and the different directions and points of observation, the differences between the building in the simulation and the photograph are not noticeable.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of mapping the accuracy of the 3D model of the designed object on the resulting photometric calculations is presented in articles [10][11][12]. Studies of the effects of reflectance and transmittance of facade coating materials on the luminance values obtained are presented in publications [11,13].…”
Section: Introductionmentioning
confidence: 99%